2020
DOI: 10.3390/w12102694
|View full text |Cite
|
Sign up to set email alerts
|

How Did the Late 1980s Climate Regime Shift Affect Temperature-Sensitive Fish Population Dynamics: Case Study of Vendace (Coregonus albula) in a Large North-Temperate Lake

Abstract: The population dynamics of fish in northern lakes is strongly influenced by climatic factors. In this study, we investigated whether there is a link between the late 1980s climate regime shift in Europe and the collapse of vendace (Coregonus albula) population at the same time in Lake Peipsi. Until the end of the 1980s, vendace was very abundant in the lake, but then its catches sharply declined. This decline inspired investigations into the extreme weather events preceding the vendace collapse using data on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
0
14
0
2
Order By: Relevance
“…Fish community in a large shallow lake such as Peipsi responds not so much to a long-term slow rise in yearly average water temperature as to short-term extreme weather events, e.g., heat waves, accompanied by cyanobacterial blooms, anoxia during night, and fish kills (Kangur et al 2013). An abrupt increase in water temperature recorded at the end of 1980s was linked to the collapse of vendace population: the hot summer of 1988, which was accompanied by a severe cyanobacterial bloom and extensive fish kill, and the subsequent non-permanent ice cover and early ice-offs in 1989 and 1990 in Lake Peipsi were the main reasons for the disappearance of vendace from catches in 1991 (Kangur et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fish community in a large shallow lake such as Peipsi responds not so much to a long-term slow rise in yearly average water temperature as to short-term extreme weather events, e.g., heat waves, accompanied by cyanobacterial blooms, anoxia during night, and fish kills (Kangur et al 2013). An abrupt increase in water temperature recorded at the end of 1980s was linked to the collapse of vendace population: the hot summer of 1988, which was accompanied by a severe cyanobacterial bloom and extensive fish kill, and the subsequent non-permanent ice cover and early ice-offs in 1989 and 1990 in Lake Peipsi were the main reasons for the disappearance of vendace from catches in 1991 (Kangur et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Shifts in the abundance of exploited species are expected to affect their availability to fisheries, as already observed in freshwater fisheries in Europe (see, e.g., Jeppesen et al 2012;Sandström et al 2014). In Lake Peipsi, the effects of high water temperatures (e.g., heat waves) in summer and extreme ice conditions on the abundance of some targeted species, e.g., lake (dwarf) smelt (Osmerus eperlanus) ) and vendace (Coregonus albula) (Kangur et al 2020), have been identified. However, a climate change signature for the entire fisheries of Lake Peipsi has so far not been detected.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations